Building Environmental Literacy: A Green Literacy Bootcamp Model for an Eco-School within a Coastal Community - Rizki Nor Amelia; Sri Ngabekti; Putri Alifa Kholil; Abdul Jabbar; Prasetyo Listiaji (Yayasan Keluarga Guru Mandiri, 2025)
Coastal schools are highly vulnerable to the impacts of climate change, including tidal flooding, erosion, and seawater intrusion, which disrupt educational processes and compromise community resilience. Strengthening environmental literacy within the eco-school framework is therefore essential to develop adaptive knowledge, critical thinking, and sustainable behavior among students. This community service project implemented a Green Literacy Bootcamp at SMP Negeri 25 Semarang, involving 45 students identified as prospective Green Warriors. The program comprised three phases: a two-day intensive training, a three-month follow-up, and a final reflection. Activities included communication workshops, creative campaigns, eco-project simulations, and student-led projects on waste management, urban farming, and tidal flood mitigation. The program was evaluated using a pre-post environmental literacy test and structural model analysis, complemented by a satisfaction survey. Results showed a substantial improvement in environmental literacy, with the largest gains observed in environmental hope and cognitive skills. Students also reported high satisfaction with the learning experience. This study contributes to the field of environmental education by offering a validated and replicable model for strengthening multidimensional environmental literacy and supporting eco-school development in coastal communities facing climate change challenges.